Optimální medikamentózní léčba vs. revaskularizace u stabilní anginy pectoris: soupeření pokračuje - Schömig, Albert (Clinical Cardiology Alert, 2008)
This study assessed the impact on long-term mortality of percutaneous coronary intervention (PCI) versus medical treatment in patients with symptoms or signs of myocardial ischemia but no acute coronary syndrome. BACKGROUND: The impact of PCI on the long-term prognosis of patients with stable coronary artery disease has not been established. METHODS: We identified 17 randomized trials comparing a PCI-based invasive treatment strategy with medical treatment in 7,513 patients with symptoms or signs of myocardial ischemia but no acute coronary syndrome. Of these patients, 3,675 were assigned to the PCI group and 3,838 to the medical treatment group. The primary end point was all-cause death. The length of follow-up was in the range between 12 and 122 months, 51 months on average. RESULTS: In the PCI group, 271 patients died compared with 335 patients in the medical treatment group, which corresponds to a 20% reduction in the odds ratio (OR) of all-cause death (OR: 0.80; 95% confidence interval [CI]: 0.64 to 0.99, p = 0.263 for heterogeneity across the trials). Allocation to the PCI group was associated with a nonsignificant 26% reduction in the OR of cardiac death (OR: 0.74, 95% CI: 0.51 to 1.06). In the PCI group, 319 patients had a nonfatal myocardial infarction after randomization compared with 357 patients in the medical treatment group (OR: 0.90, 95% CI: 0.66 to 1.23). CONCLUSIONS: These findings suggest that a PCI-based invasive strategy may improve long-term survival compared with a medical treatment-only strategy in patients with stable coronary artery disease.
Keywords: randomizované kontrolované studie jako téma; Randomized Controlled Trials as Topic; lidé; nemoci koronárních tepen; Treatment Outcome; balónková koronární angioplastika; výsledek terapie; Angioplasty, Balloon, Coronary; Coronary Artery Disease; Humans